Studi Komparatif Respons Energi dan Sensitivitas TLD-100 dan TLD-100H pada Radiasi Foton LINAC 6 MV - Ega Salsa Billa; Aulia Gamboa Rodriques; Erlinda Ratnasari Putri (Progressive Physics Journal, 2026)
Accurate radiation dose measurement is essential in radiotherapy dosimetry, particularly for treatments delivered using 6 MV photon beams from a Linear Accelerator (LINAC). Thermoluminescent dosimeters (TLDs) are extensively used in clinical practice due to their small dimensions, near tissue-equivalent response, and reliable dosimetric performance. Among these, TLD-100 (LiF:Mg,Ti) has long been established as a reference dosimeter, while TLD-100H (LiF:Mg,Cu,P) has been developed to provide enhanced sensitivity. This study presents a comparative evaluation of the energy response and sensitivity of TLD-100 and TLD-100H under 6 MV LINAC photon irradiation, based on a critical review of previous experimental, Monte Carlo, and clinical studies. The reviewed results indicate that TLD-100 exhibits a stable energy response with relatively low energy dependence in high-energy photon beams, supporting its suitability for clinical dose verification. In contrast, TLD-100H demonstrates markedly higher sensitivity, making it particularly advantageous for low-dose and scattered radiation measurements, albeit with increased susceptibility to variations in irradiation conditions and calibration procedures. These findings highlight that the choice of thermoluminescent dosimeter in radiotherapy should be guided by the intended dosimetric application, with careful consideration of the balance between energy response stability and sensitivity.